PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALLY (TAI) TERHADAP PRESTASI BELAJAR DI KELAS IV - Sunartin Sunartin (Dharmas Education Journal (DE_Journal), 2021)
This analysis is motivated because the learning outcomes of students are still many. The criteria have not reached Minimum Completeness (KKM), therefore the learning applied by the teacher is still not optimal and the learning model used does not vary, so students will feel boredom so they are not interested in the process of demanding knowledge in the group. The analysis in this study intends to be able to apply the form of cooperative learning type Team  Individually () so that the reaction of students to study in class IV is more effective, especially the area where I live, theme 8. This type of research is classroom action research. The subjects of this study were Class IV students of SD Negeri 089x Tanjung Solok in the first semester (one) of the 2020/2021 academic year. The types of data in this research are quantitative data and qualitative data. Quantitative data is in the form of learning outcomes obned from tests conducted at the end of each meeting while qualitative data is data in the form of observation sheets. The results showed an increase in the learning outcomes of fourth grade students at SDN SDN Tanjung Solok in each cycle, the classical completeness score in the first cycle was 43.75% with an average of 63.43 increased to 75% with an average of 70.31 in the first cycle. II, the increase in learning outcomes from cycle I to cycle II is 6.88% and has achieved classical completeness equal to or more than 65%..